WT1 Interacts with MAD2 and Regulates Mitotic Checkpoint Function - Shandilya, Jayasha (2014)
Tumor suppressors safeguard the fidelity of the mitotic checkpoint by transcriptional regulation of genes that encode components of the mitotic checkpoint complex (MCC). Here we report a new role for the tumor suppressor and transcription factor, WT1, in the mitotic checkpoint. We show that WT1 regulates the MCC by directly interacting with the spindle assembly checkpoint protein, MAD2. WT1 colocalizes with MAD2 during mitosis and preferentially binds to the functionally active, closed-conformer, C-MAD2. Furthermore, WT1 associates with the MCC containing MAD2, BUBR1 and CDC20, resulting in prolonged inhibition of the anaphase promoting complex/cyclosome (APC/C), and delayed degradation of its substrates SECURIN and CYCLIN B1. Strikingly, RNAi-mediated depletion of WT1 leads to enhanced turnover of SECURIN, decreased lag time to anaphase, and defects in chromosome-segregation. Our findings identify WT1 as a regulator of the mitotic checkpoint and chromosomal stability.